The E3 ligase BRUTUS facilitates degradation of VOZ1/2 transcription factors. (16th July 2018) - Selote, Devarshi; Matthiadis, Anna; Gillikin, Jeffrey W.; Sato, Masa H.; Long, Terri A.
Abstract: BRUTUS (BTS) is an iron binding E3 ligase that has been shown to bind to and influence the accumulation of target basic helix‐loop‐helix transcription factors through 26S proteasome‐mediated degradation in Arabidopsis thaliana . Vascular Plant One‐Zinc finger 1 (VOZ1) and Vascular plant One‐Zinc finger 2 (VOZ2) are NAM, ATAF1/2 and CUC2 (NAC) domain transcription factors that negatively regulate drought and cold stress responses in plants and have previously been shown to be degraded via the 26S proteasome. However, the mechanism that initializes this degradation is unknown. Here, we show that BTS interacts with VOZ1 and VOZ2 and that the presence of the BTS RING domain is essential for these interactions. Through cell‐free degradation and immunodetection analyses, we demonstrate that BTS facilitates the degradation of Vascular plant One‐Zinc finger 1/2 (VOZ1/2) protein in the nucleus particularly under drought and cold stress conditions. In addition to its known role in controlling the iron‐deficiency response in plants, here, we report that BTS may play a role in drought and possibly other abiotic stress responses by facilitating the degradation of transcription factors, VOZ1/2. Abstract : The transcription factors Vascular Plant One‐Zinc finger 1 (VOZ1) and Vascular plant One‐Zinc finger 2 (VOZ2) regulate the expression of a number of genes involved in biotic and abiotic stress response in plants. Upon translocation to the nucleus, VOZ2 is subjected to 26S proteasome‐mediated degradation. In this study, we provide evidence that BRUTUS (BTS), an E3 ligase, facilitates the degradation of VOZ2, consequently overexpression of BTS phenocopies that of loss of VOZ function during drought stress. Our work sheds new light on how VOZ proteins are regulated posttranscriptionally and opens the door for further exploration of ways to develop plants with elevated tolerance to changing environmental conditions.